Development and Validation of the Binge Eating Disorder Scale (BEDS) - Arauco-Lozada, Tania; Yupanqui-Lorenzo, Daniel E.; Ottiniano-Malaga, Tatiana (Nutrición Clínica y Dietética Hospitalaria, 2024)
Objective: Binge Eating Disorder (BED) is one of the most frequent eating disorders presentations. The primary symptom is recurrent episodes of binge eating, characterized by a large amount of food in a short period and a sense of losing control over eating. BED could contribute to the development of obesity and its complications. The study aimed to design and validate a scale to identify risk behaviors for BED. Methods: An instrumental design was used to describe the development and initial validation of the new brief scale, BEDS. Participants were 345 adults who completed the self-report questions and reported BED episodes in the past three months. Results: The BEDS was initially composed of 10 items to ended up with 6 items due to analysis and exploratory factor analysis (EFA). In the analysis process, 3 models were explored within which a unidimensional model with 6 items was maintained. Likewise, reliability was adequate (α = 0.922; ω = 0.924). On the other hand, it was proved that the instrument correctly assesses binge eating behavior when comparing groups, where it was obtained that those who had identified episodes of binge eating in their life maintained higher averages in the test than those who did not present this problem. Similarly, there were more episodes in women than in men, and in those who presented burnout. Conclusion: BEDS demonstrated adequate psychometric properties and is useful for future research.